2023
DOI: 10.1371/journal.pone.0287379
|View full text |Cite
|
Sign up to set email alerts
|

Effect of core training on athletic and skill performance of basketball players: A systematic review

Abstract: A limited number of studies focus on the effect of core training on basketball players’ athletic performance and skills. This systematic reviewaimed to comprehensively and critically review the available studies in the literature that investigate the impact of core training on basketball players’ physical and skill performance, and then offer valuable recommendations for both coaches and researchers. Thedata collection, selection, and analysis adhered to the PRISMA protocol. English databases, including Ebscoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…FT exercises like squats, lunges, and plyometric drills (e.g., box jumps, and squat jumps) can improve lower body strength and power, leading to a more explosive and effective shooting motion. Regarding the improvement of dribbling performance, the core strength increased by FT may contribute to execution with this activity ( Luo et al, 2023 ). A strong and stable core is essential for maintaining balance and control while dribbling, especially when under defensive pressure ( Moselhy, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FT exercises like squats, lunges, and plyometric drills (e.g., box jumps, and squat jumps) can improve lower body strength and power, leading to a more explosive and effective shooting motion. Regarding the improvement of dribbling performance, the core strength increased by FT may contribute to execution with this activity ( Luo et al, 2023 ). A strong and stable core is essential for maintaining balance and control while dribbling, especially when under defensive pressure ( Moselhy, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the improvement of dribbling performance, the core strength increased by FT may contribute to execution with this activity (Luo et al, 2023). A strong and stable core is essential for maintaining balance and control while dribbling, especially when under defensive pressure (Moselhy, 2020).…”
Section: Effect Of Ft On Basketball Skill-related Performancementioning
confidence: 99%
“…The beginning phase of the season is characterized by a relative interruption after the rest and rehabilitation period following the previous season. Studies have shown that careful preparation during this phase can improve fundamental abilities, including basic strength, flexibility, and overall body capacity, according to (Luo et al, 2023). During this time, it is important for coaches to utilize training preparation methods that enhance the foundations of physical abilities, including elements of rehabilitation in case of possible injuries, as indicated by (Bahir et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…To optimize performance in women's basketball, it is necessary to respect the principles of sports training, such as individuality and specificity, as highlighted by Mancha-Triguero et al (2020). Studies have demonstrated that a carefully tailored program, focused on developing core muscles and motor coordination, has influenced the enhancement of necessary skills for good basketball performance (Luo et al, 2023). Research has observed that incorporating game situations during training, including tactical meetings and improvised scenarios, has aided in the development of tactical awareness and the ability to make quick decisions on the field (Mancha-Triguero et al, 2020;Gabbett et al, 2009;Scalan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the weakness or loss of core muscle coordination can cause abnormal movement patterns, compensatory movement patterns, or various types of sports injuries such as muscle strain and overuse injuries [2]. Since core muscles are essential for carrying out appropriate movements by creating a stable base of support, the fatigue of these muscles may affect the performance of an individual, especially basketball players [3,4]. A study by Surenkok et al (2008) examined the effect of abdominal muscle fatigue via an isokinetic protocol, and the accumulation of lactic acid, on the static and dynamic balance of healthy individuals, concluding that muscle fatigue had a negative effect on the static and dynamic balance of the subjects [5].…”
Section: Introductionmentioning
confidence: 99%